2023
DOI: 10.21608/svuijas.2023.190521.1269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the genetic diversity in maize hybrids under drought conditions using drought indices, SSR markers, and thermal imaging

Abstract: The aim of the study was screening fourteen hybrids of maize under normal and drought stress. A field trial was carried out during two summer seasons on an experimental farm, Ismailia, Egypt. Growth, yield physiological traits have been estimated. Indices of drought resistance were calculated for each hybrid; mean productivity, drought susceptibility index, tolerance index, geometric mean productivity and yield stability index. Simple sequence repeat analysis of DNA (SSR) was applied to estimate the genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, several studies have reported the successful utilization of SSR markers to identify critical agronomic characteristics in various crops, including rice (Khan et al, 2022), soybean (Li et al, 2010), wheat (Haque et al, 2021) and maize (Belalia et al, 2019). Similarly, SSR markers have been used in genetic diversity studies of maize under drought conditions (Emam et al, 2023), identification of QTLs in oil palms (Bhagya et al, 2020), assessing the genetic purity of rice (Kumar et al, 2021) and evaluating the salt tolerance of wheat (EI-Hendawy et al, 2019). Further, photosynthetic traits in a population of rice deletion mutants (Mubarak et al, 2013), physiological and genetic evaluation in a wheat-doubled haploid population (Mubarak et al, 2008) and the presence of drought tolerance genes in maize (Sedhom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have reported the successful utilization of SSR markers to identify critical agronomic characteristics in various crops, including rice (Khan et al, 2022), soybean (Li et al, 2010), wheat (Haque et al, 2021) and maize (Belalia et al, 2019). Similarly, SSR markers have been used in genetic diversity studies of maize under drought conditions (Emam et al, 2023), identification of QTLs in oil palms (Bhagya et al, 2020), assessing the genetic purity of rice (Kumar et al, 2021) and evaluating the salt tolerance of wheat (EI-Hendawy et al, 2019). Further, photosynthetic traits in a population of rice deletion mutants (Mubarak et al, 2013), physiological and genetic evaluation in a wheat-doubled haploid population (Mubarak et al, 2008) and the presence of drought tolerance genes in maize (Sedhom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%